Третман на ортодонтските неправилности со два вида на адхезиви - Јусуфи, Газменд (Стоматолошки факултет, УКИМ, Скопје, 2017)
Introduction: Enamel decalcification or white opaque lesion on the labial side around orthodontic attachments are common problem during and following fixed orthodontic treatment. Brackets and various orthodontic elements (elastic, springs) that are used during the treatment, make the oral hygiene difficult and the accumulation in dental plaque much easier. Decalcification often follows plaque accumulation promoted by appliance components and bonding materials, subsequent acid production by the bacterial plaque result in an alteration in the appearance of the enamel surface. Co-existence of the four factors namely, bacterial plaque, fermentable carbohydrates, a susceptible tooth surface and a sufficient period of time are necessary for white opaque lesions to develop. The risk of enamel demineralization during fixed orthodontic treatment can be prevented by either eliminating the plaque deposition on the enamel surface by improving patient oral hygiene or by enhancing the enamel resistance to the microbial acid by using topical fluoride. Aim: Of this study is to conduct a comparative study of using two different adhesive materials for the application of fixed orthodontic appliances and their influence on salivary parameters by determining: change in the pH of saliva before and after the placement of fixed orthodontic device, depending of the type of adhesive used for fixing on tooth; salivary buffering capacity: determination of the concentration of bicarbonate, phosphates before and after fixing fixed orthodontic appliances; the concentration of electrolytes before and after fixing of fixedorthodontic appliances; the concentration of cariogenic microorganisms such as Streptococcus Mutans and Streptococcus Sobrinus on the plaque around the brackets; concentration of salivary fluoride before and after placement of fixed orthodontic appliances; changes in the enamel structure depending on the material used for fixing fixed orthodontic appliances. Material and methods: In order to realize our goal we included 60 patients with different types of malocclusions who need orthodontic treatment. We classified the patients into two groups: - in the first group of 30 patients, the composite adhesive (ConTec Go, Dentaurum, Германија) was used for fixing brackets, while - glass-ionomer adhesive (GC Fuji Ortho LC, GC Amerika, САД) was used in the second group of 30 patients. As a material for testing the concentration of electrolytes, we used the saliva of patients we collected in sterile tubes at three time intervals: before placing the brackets, 24 hours after installation and 1 month from the start of treatment. Results: pH of saliva had a significantly lower value when using a composite adhesive comparing using a glass-ionomer adhesive. The results of this study showed that the fluoride concentration increased significantly 24 hours after placement of brackets in patients using glas-ionomer adhesive. This concentration is gradually reduced one month after placement. The situation was different in patients with composite adhesive. The bioactive properties of fluoride-releasing materials used for adhesion of brackets during fixed orthodontic treatment were also confirmed by CEM, manifested as intense inhibition of demineralization of the enamel. Conclusion: Based on the analysis of the results obtained from the studies carried out within this study, it can be concluded that in order to preserve the dental health, in particular, the integrity of the enamel during the fixed-orthodontic treatment period, the application of appropriate preventive measures is imperative. The expected effect of these measures is the inhibition of the demineralization processes of the enamel. In this relation, the basic meaning is the practice of solid oral hygiene by the patient, but the need for occasional professional plaque removal in these patients must also be emphasized. Additive effect in inhibiting the demineralization process of enamel fixed orthodontic treatment is achieved by the application of adhesives that contain and continuously, in small quantities, release certain elements with a protective role in relation to caries.
Докторска дисертација одбранета во 2017 година на Стоматолошкиот факултет во Скопје, под менторство на проф. д–р Мира Јанкуловска.
Keywords: brackets, glass-ionomer cements, demineralization, fluoride.